KONSEP ISLAM DALAM AL-TANZIL AL-HAKIM PERSPEKTIF MUHAMMAD SYAHRUR - Affandi, Abdullah (Jurnal al Hikmah, 2015)
Most of the Muslims, according Shahrur, are misled by the various ideas from classical tradition, regardless of the variety of contemporary scientific discoveries. They consider various classical scientific tradition-filled doctrine as a truth that is "come down from the sky" and transformed into the absolute truth, including the understanding of the term Islam. So important for Shahrur to redefine the concept of Islam and with direct reference to al-Tanzil (Quran) as the main source of Islam itself. Shahrur calls on Muslims to study the verses of the Koran that talks about Islam as a preliminary step to find the correct understanding, valid, and comprehensive. This is an writerâs interesting to try to assess Shahrurâs bid to rereading and redefinition of the concept of Islam that had been considered complete.